2019
DOI: 10.1037/fam0000568
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about you baby: Expectant parents’ narratives suggest prenatal spillover for fathers.

Abstract: The coherence of parents' narratives about their children, which is the extent to which descriptions are accepting, consistent and complex, are thought to reflect optimal information processing of interpersonal relations and as such facilitate sensitive and responsive parenting. However, despite recent meta-analytic findings that have demonstrated links between the nature of prenatal thoughts and feelings about the unborn infant and later parenting, studies have yet to examine the narrative coherence of expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…Especially, mothers and fathers who have aforementioned risk factors present more disengaged narratives about their infants after the baby is born (Vreeswijk et al 2015). In addition to these findings, when the coherence in parents' narratives were examined, it was found that unsatisfactory feelings toward life and having a low interparental relationship quality was a risk factor for fathers' incoherent narratives about their baby (Foley et al 2019). As a recent and inclusive study which involved both fathers' and mothers' representations, Vismara et al (2021) showed that there is a correlation between prenatal representations of both parents and their perception about their infants' temperament.…”
Section: Various Factors Linked To Representations Of Parentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Especially, mothers and fathers who have aforementioned risk factors present more disengaged narratives about their infants after the baby is born (Vreeswijk et al 2015). In addition to these findings, when the coherence in parents' narratives were examined, it was found that unsatisfactory feelings toward life and having a low interparental relationship quality was a risk factor for fathers' incoherent narratives about their baby (Foley et al 2019). As a recent and inclusive study which involved both fathers' and mothers' representations, Vismara et al (2021) showed that there is a correlation between prenatal representations of both parents and their perception about their infants' temperament.…”
Section: Various Factors Linked To Representations Of Parentsmentioning
confidence: 93%
“…In conclusion, the mothers' own attachment experiences with their mothers, negative memories about their childhood (George and Solomon 1996, Huth-Bocks et al 2004, Sokolowski et al 2007), parents' evaluations and expectations in prenatal period (Buldur 2009, Vreeswijk et al 2015, Foley et al 2019, Hacıoğlu 2020, psychological problems (Pajulo et al 2001, Wood et al 2004, Muzik et al 2013, and various factors which are related with the child such as sleep and eating problems, learning disorders, disability, and ADHD (Benoit et al 1997a, Coolbear and Benoit 1999, Button et al 2001, Vreeswijk et al 2012, Darling Rasmussen et al 2019) are important risk factors for parents' negative representations toward their children. Besides, Rosenblum et al (2002) pointed out that parenting behaviors have a mediator role on the relationship between representations of mothers and the actions of their children.…”
Section: Various Factors Linked To Representations Of Parentsmentioning
confidence: 95%
“…A narrativa de Ana (Casal 02), por exemplo, demonstrou como ver o marido envolvido com a gestação e o bebê contribuiu para que ela também se sentisse mais segura quanto à sua relação conjugal. Essa interpretação está alinhada aos resultados obtidos por Foley et al (2019), que sugerem que o spill-over, ou seja, o transbordamento entre conjugalidade e coparentalidade, inicia-se ainda durante a gravidez. Segundo esses autores, pais que descreveram piores qualidades de vida e conjugal tenderam a também a apresentar maior dificuldade para falarem sobre o seu bebê durante a gestação.…”
Section: A Gravidezunclassified